Análise da relação entre apego ao lugar, satisfação e fidelidade dos visitantes em destinos turísticos ambientais: um estudo em Fernando de Noronha/PE - Santoro, Monica Almeida Gavilan (2014)
The competition among tourist destinations environmental generates the emergent need to find different strategies to close down if the purpose of delight and retain their visitants. A customer satisfaction, loyalty and the development of attachment to place form a solid compound in search of promotion a tourist destination. This study presents the general objective analysis of the relationship between attachment to place, satisfaction and loyalty of visitors, in the archipelago of Fernando de Noronha / PE. Therefore, a model will be used as reference, where they will be analyzed various constructs related to attachment to place, satisfaction and loyalty, as well as the relations between them. The methodology used in the study consists of an exploratory, descriptive, where the sample is random and consists of individuals who visited Fernando de Noronha on a pre-defined period of ten days. Based on a sample table, we defined a quantitative equivalent of 246 questionnaires, which will be applied when the visitor leaves the destination, the departure lounge of airport. A proposal focuses on the possibility to get results able to understand the subjective and intriguing relationship that involves the triad attachment to place, satisfaction and loyalty, trying to thus provide subsidies for optimizing environmental tourist destination